2022
DOI: 10.1093/eurheartj/ehac494
|View full text |Cite
|
Sign up to set email alerts
|

Empagliflozin in acute myocardial infarction: the EMMY trial

Abstract: BACKGROUND AND AIMS Sodium–glucose co-transporter 2 inhibition reduces the risk of hospitalisation for heart failure and for death in patients with symptomatic heart failure. However, trials investigating the effects of this drug class in patients following acute myocardial infarction are lacking. METHODS In this academic, multicentre, double-blind trial, patients (n = 476) with acute myocardial infarction accompanied by a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
118
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(123 citation statements)
references
References 52 publications
3
118
0
2
Order By: Relevance
“…Remarkably, most of these effects discussed previously could be related to persistent molecular and metabolic changes since all patients had been treated with SGLT2-I for at least 3 months before the AMI. Indeed, the recently published EMMY trial did not find any difference in acute troponin values between the SGLT2-I treated and untreated cohorts [ 9 ]. However, the EMMY trial included only a minority of diabetic patients, and all patients were randomized to the treatment at the time of the AMI admission, for only 3 days, rather than receiving SGLT2-I some months earlier as in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, most of these effects discussed previously could be related to persistent molecular and metabolic changes since all patients had been treated with SGLT2-I for at least 3 months before the AMI. Indeed, the recently published EMMY trial did not find any difference in acute troponin values between the SGLT2-I treated and untreated cohorts [ 9 ]. However, the EMMY trial included only a minority of diabetic patients, and all patients were randomized to the treatment at the time of the AMI admission, for only 3 days, rather than receiving SGLT2-I some months earlier as in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have also shown that SGLT2-I mitigates acute myocardial I/R injury, attenuating cardiac infarct size, increasing left ventricular function, and reducing arrhythmias [ 6 , 7 ]. There are some ongoing trials, compounded by the first published results of the EMMY Trial, which did not find any difference in acute troponin values between the SGLT2-I treated and untreated cohorts [ 8 , 9 ]. However, the EMMY trial included only a minority of diabetic patients, and all patients were randomized to the treatment at the time of the AMI admission.…”
Section: Introductionmentioning
confidence: 99%
“…In the retrospective analysis conducted by Zhu et al, patients treated with dapagliflozin after AMI had a significantly lower rate of major adverse cardiovascular events, including overall deaths, HF, MI, stroke and unplanned repeat revascularization compared to the DAPA-free group [ 112 ]. According to the EMMY trial results introducing 10 mg empagliflozin once daily for patients that underwent recent AMI with PCI, it is associated with a significantly greater NT-proBNP reduction over 26 weeks, accompanied by a significant improvement in echocardiographic parameters [ 113 ]. Although the long-term benefits of SGLT-2is are particularly compelling, the Baker et al study [ 114 ] demonstrated that their short-term effects may also determine favourable treatment outcomes.…”
Section: Sglt-2is In Dc—the Overview Of Research Resultsmentioning
confidence: 99%
“…Interestingly, the SGLT2i results on ISR were independent of glycemic control suggesting that SGLT2 inhibitors might favorably affect the coronary remodeling after stent implantation, possibly through the regulation of a large range of metabolic, molecular, and hemodynamic mechanisms irrespectively of their glucose-lowering effects [ 8 , 12 , 13 ]. Indeed, previous studies showed that in patients with T2DM and AMI, SGLT2i reduced infarct size and peri-infarct tissue inflammation [ 14 ], preventing also the loss of pump function expressed as LVEF [ 15 ]. These data might suggest that the anti-inflammatory effect of SGLT2i eventually contribute to their putative protective effect against restenosis.…”
Section: Discussionmentioning
confidence: 99%